A rituális kommunikáció neodurkheimi elmélete és a média (Szociológiai Szemle, 2024)
Until recently the Durkheimian perspective has been underestimated in communication researches. This work explores how a rediscovered Durkheimian sociology is capable of providing a solution to numerous unsolved problems raised by media researchers. In the course of discussion the paper compares the Neo-Durkheimian moral philosophy with Michael Foucault's social theory. Reviewing the English language literature on rituals the article sees an answer to whether it is possible to use the category of ritual in modern societies. The answer is positive, since media rituals can be regarded as symbolic moral dramas, which provide a public performance of the conflicts of the community.